Corrosion Rate of Ship Fuel Pipes Due to the Use of HSD B0 and HSD B30 - Tubagus Nur Ilham; Dwisetiono (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2024)
Pipes are an important part of the world of shipping because most ships use pipes as a medium for transferring liquids from one tank to another or from one place to another. The use of biodiesel B30 as a mixture of diesel fuel high speed diesel (HSD) has an impact on the engine and other components. The method used in calculating the corrosion rate is the loss method which refers to the ASTM G31-71 standard using a test kit flow loop and potentiostat. Corrosion rate obtained by using a test toolflow loop until the 75th day that the B0 corrosion rate was 0.003534 mm/y and the B30 corrosion rate was 0.0047366 mm/y. The corrosion rate obtained by using a potentiostat corrosion testing tool showed that the B0 corrosion rate was 0.00000016 mm/y and the B30 corrosion rate was 0.00000963 mm/y. There is an additional 30%fatty acid methyl ester (FAME) palm crude oil can increase the corrosion rate.